Tinerii, educație și ocupație în România - Neagu, Gabriela (Calitatea Vieții, 2015)
Compared to other states, Romania has an important advantage: human resource: over six million of the population in the country are young persons aged between 14–35 years. Efficient utilisation of the human resource is carried out through education and employment, but quite in these chapters Romania has to overcome great obstacles: many young people leave the education system prematurely, what is being taught in school is far from what is required in the labor market, access to the labor market for young people is perceived as being a strictly individual responsibility, and not one of a social nature etc. In this article we will examine the relationship between education and occupation in Romania, from the point of view of socio-economic level to that of young people. From a theoretical point of view, the relationship between education and occupation will be discussed using the theories of sociology and economy: human capital theory, the theory inequality of chances of access to education, signal theory etc. From the empirical point of view, we will use Romanian quantitatively research data from the last few years, which included the educational – occupational topic, as well as data from INS and IRES, specialized in gathering and procesing statistical data.